2020
DOI: 10.3390/v12050566
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide–Virus Interactions in Honey Bees: Challenges and Opportunities for Understanding Drivers of Bee Declines

Abstract: Honey bees are key agricultural pollinators, but beekeepers continually suffer high annual colony losses owing to a number of environmental stressors, including inadequate nutrition, pressures from parasites and pathogens, and exposure to a wide variety of pesticides. In this review, we examine how two such stressors, pesticides and viruses, may interact in additive or synergistic ways to affect honey bee health. Despite what appears to be a straightforward comparison, there is a dearth of studies examining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 175 publications
0
39
0
Order By: Relevance
“…The interaction of multiple factors makes it more di cult to understand the reasons for the decline in insect pollinators. Some insecticides can exert additive or synergistic effects on virus-induced mortality and replication in honey bees by affecting their immune system [12]. Diet and virus infection are related in honey bee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of multiple factors makes it more di cult to understand the reasons for the decline in insect pollinators. Some insecticides can exert additive or synergistic effects on virus-induced mortality and replication in honey bees by affecting their immune system [12]. Diet and virus infection are related in honey bee.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality food can help honey bee ght viruses. Some insecticides can increase the sensitivity of bees to viruses by affecting their immune mechanism [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the extensive work already published on bees: -Straub et al (2020) show that neonicotinoids and ectoparasitic mites act synergistically to weaken honey bee colonies and contribute to colony collapse. -Two literature reviews (Harwood and Dolezal, 2020;O'Neill et al, 2018) document the harmful interactions between pesticides (including neonicotinoids) and immunity to pathogens and parasites. -Paleolog et al (2020) showed the effects of imidacloprid may affect proteolysis, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and global DNA methylation in honeybees.…”
Section: Sub-lethal and Synergistic Effectsmentioning
confidence: 99%
“…Since 2007, beekeepers have been reporting high annual colony losses (vanEngelsdorp et al, 2007(vanEngelsdorp et al, , 2008Kulhanek et al, 2017) caused primarily by stress due to parasitic infestations (Neumann and Carreck, 2010;Steinhauer et al, 2021), pathogenic infections (Berthoud et al, 2010), poor nutrition (Leonhardt and Blüthgen, 2012;Donkersley et al, 2014), and exposure to pesticides (Sanchez-Bayo and Goka, 2014;Dively et al, 2015). These ubiquitous and interacting stressors have been shown to negatively affect various aspects of honey bee health including larval and pupal development (Wu et al, 2011;Chen et al, 2016), longevity (Wu et al, 2011;DeGrandi-Hoffman and Chen, 2015), immune function (Nazzi and Pennacchio, 2018;Harwood and Dolezal, 2020), and memory (van Dame et al, 1995;Siviter et al, 2018). Perhaps one of the more troubling and cryptic effects of these stressors relate to disruptions in the performance of important honey bee social behaviors and alterations to the expected pattern of temporal polytheism (Tasei, 2001;Thompson et al, 2007;Fine and Corby-Harris, 2021).…”
Section: Introductionmentioning
confidence: 99%